SISTEM INFORMASI PENJADWALAN KURSUS BERBASIS WEBSITE PADA LPK PERWIRA - Saghifa Fitriana; aprih widayanto; dena dhaifina ishmah (Indonesian Journal of Networking and Security (IJNS), 2021)
In today's globalization era, information technology is progressing rapidly which is the equipment created to facilitate human work especially in the field of education and support the activities of teaching and learning process. Working Training Institute (LPK) Perwira Purbalingga requires once an information system that supports the learning process especially in the scheduling of courses so as to facilitate students in viewing the course schedule. For that reason the author tried to create an end task regarding the scheduling system at the Working Training Institute (LPK) Perwira Purbalingga. The design of this information system is the best solution to solve the problems that exist in this institution. In this research the authors use waterfall methods, as well as the process of collecting data by means of observation, interviews and library studies. With a computerized system can make it easy for students and coaches to access the course schedule. Keywords: Information Systems, System Scheduling Courses, LPK Perwira